Ultra‐performance liquid chromatography–tandem mass spectrometry determination and pharmacokinetic studies of five phenolic acids in rat plasma after intravenous administration of salvianolic acid for injection. (15th November 2022) - Feng, Cuiyue; Yang, Ting; Wei, Xiyu; Liu, Houru; Zhang, Zhenzhen; Zhang, Zhifei; Li, Wei
Abstract: A simple, efficient, and sensitive ultra‐performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method was developed and validated for simultaneous determination and pharmacokinetic study of salvianolic acid D, rosmarinic acid, lithospermicic acid, salvianolic acid B, and salvianolic acid Y in rat plasma after intravenous administration of salvianolic acid for injection. Three doses of administration, containing 10, 25, and 62.5 mg/kg, were investigated. Plasma samples were pretreated using protein precipitation with pre‐cooled acetonitrile. As shown in S1, Chromatographic separation was achieved on a Waters Acquity UPLC® BEH C18 column (1.7 μm, 2.1 × 100 mm) with a mobile phase composed of acetonitrile‐methanol‐0.5% aqueous formic acid (10:30:60, v/v/v) at a flow rate of 0.3 ml/min. MS was detected by electrospray ion source negative ion mode and multiple reaction monitoring mode. The method was fully validated. The calibration curves for the five phenolic acids were linear in the given concentration ranges. The extraction recoveries, matrix effects, intra‐day and inter‐day precisions, and accuracies of the five analytes were all within acceptable limits. No significant difference of elimination half‐life time ( T 1/2 ) of five analytes at three doses was observed. Area under the curve and peak concentration ( C max ) of the five analytes demonstrated a linear increase in the doses with the linear correlation r of each analyte at three doses being greater than 0.915. It indicated that the pharmacokinetic behavior of is positively related to the dose in the range of 10–62.5 mg/kg.